Late cardiovascular drift observable during ultraendurance exercise - Mattson, C. M.; Stahlberg, M.; Larsen, F. J.; Braunschweig, F.; Ekblom, B. (Medicine & Science in Sports & Exercise, 2011)
Introduction: The present study investigates the adaptation of the central circulation to ultraendurance exercise, including the relative contributions of changes in stroke volume (SV) and arteriovenous oxygen difference to the increased oxygen pulse (VO2/HR). Methods: We evaluated subjects undergoing 12 h of mixed exercise at controlled intensity (n = 8) and a 53-h adventure race (n = 20). HR, oxygen uptake (VO2), and cardiac output determined using noninvasive gas rebreathing were measured during cycling at a fixed work rate after 0, 4, 8, and 12 h and 0, 20, and 53 h of continuous exercise in the 12- and 53-h protocols, respectively. Results and Conclusions: The central circulation changed in several steps in response to ultraendurance exercise. Compared with initial levels, V?O2 was increased at every time point measured. The increase was attributed to peripheral adaptations, confirmed by a close correlation between change in VO2 and change in arteriovenous oxygen difference. The first step of the circulatory response was typical of normal (early) cardiovascular drift, with increased HR and concomitantly decreased SV and VO2/HR, occurring during the first 4-6 h. The second step, which continued until approximately 12 h, included reversed HR drift, with normalization of SV and VO2/HR. When exercise continued until 50 h, late cardiovascular drift was noted, characterized by increased VO2/HR (indicating more efficient energy distribution), decreased peripheral resistance, increased SV, and decreased work of the heart. Because cardiac output was maintained at all time points, we interpret the changes as physiologically appropriate adaptations to ultraendurance exercise.